2009
DOI: 10.1016/j.ejca.2009.09.014
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-29a regulates the expression of numerous proteins and reduces the invasiveness and proliferation of human carcinoma cell lines

Abstract: Subsequent studies using siRNA to knock down several candidate proteins from the 2D DIGE experiment identified RAN (a member of the RAS oncogene family) which significantly reduced the invasive capability of a model lung cancer cell line.We conclude that miR-29a has a significant anti-invasive and anti-proliferative effect on lung cancer cells in vitro and functions as an anti-oncomir. This function is likely mediated through the post-transcriptional fine tuning of the cellular levels of several proteins, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 33 publications
3
67
0
1
Order By: Relevance
“…The three miR-29 isoforms are arranged in two clusters: miR-29b1/miR-29a located on chromosome 7q32 and miR-29b2/miR-29c located on chromosome 1q32. miR-29a has been shown to reduce invasiveness and proliferation of human carcinoma cell lines (Muniyappa et al, 2009). miR-29b was previously correlated with good prognosis in patients with acute myeloid leukemia, and has a tumor suppressor function in leukemic blasts by targeting apoptosis, cell cycle and proliferation pathways (Garzon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The three miR-29 isoforms are arranged in two clusters: miR-29b1/miR-29a located on chromosome 7q32 and miR-29b2/miR-29c located on chromosome 1q32. miR-29a has been shown to reduce invasiveness and proliferation of human carcinoma cell lines (Muniyappa et al, 2009). miR-29b was previously correlated with good prognosis in patients with acute myeloid leukemia, and has a tumor suppressor function in leukemic blasts by targeting apoptosis, cell cycle and proliferation pathways (Garzon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miR-29a expression has been found in colorectal, gastric, and lung cancers, acute myeloid leukemia, and lymphoma. 13,[15][16][17][18] Furthermore, a significant downregulation TRIM68 is a target of miR-29a and miR-1256 and was upregulated in PCa. By comparing computerized prediction of miRNA targets with mRNA microarray analysis, we found that TRIM68 could be a target of both miR-29a and miR-1256.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both PGK-1 and AR genes are located within Xqll-Xql3 region and PGK-1 short tandem repeat polymorphism linkage to AR in the expression of miR-29a has been found to be correlated with short survival, more invasive phenotype, and early recurrence. [16][17][18] Therefore, miR-29a is believed to play important roles in the inhibition of cancer development and progression and the loss of its expression is in part responsible for tumor development and progression. However, there is no report on the expression level of miR-29a in PCa cells, normal prostate epithelial cells, human PCa specimens or normal human prostate tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Five of these miRNA have been reported to be oncogenic and two of the miRNA are believed to have tumor-suppressive functions (Table 1). (15,(17)(18)(19)(20)(21)(22)(23)(24) Compartment-specific miRNA overexpression was not detected in the liver invasion front with respect to the same miRNA in the liver, the tumor invasion front or the tumor center. Similarly, expression analysis of samples taken from the tumor invasion front was compared with samples taken from pure liver, the liver invasion front or the tumor center.…”
Section: Resultsmentioning
confidence: 98%